PENGARUH SISTEM PENGENDALIAN INTERN PIUTANG TERHADAP PENAGIHAN PIUTANG USAHA PADA PT. DINAMISATOR PALEMBANG - Sahila . (JURNAL KOMPETITIF, 2013)
ABSTRACT Based on the research result of internal control system receivables patrial tets to the effectiveness of collection of accounts receivables at P.T. Dinamisator trough discussion that the internal control which consist of enviroment, risk assesment, control activities, information and communication and monitoring there is a conclution that the significant effect come from the enviroment variable (X1) in the amount of 58%. There is a condution obtained from the simulateneous tets that there is a significant effect between enviroment control, risk assesment, control activities, information and communication and also monitoring to effectiveness of collection of account receivables.This is shown by the acquistion value of the F tets whith shown a rejection of H0, so from the condusion suggested the P.T.Dinamisator to get more attention and improve the inviroment control whith aimed to minimized the uncollectible receivable. Keyword : Enviroment Control, Risk Assement, Information, communication and monitoring